A Cohort study on Completion of Treatment and the Factors Affecting Adherence to the TB DOT Center Treatment Plan Among Patients with Tuberculosis - Yumiaco, Evelyn B.
Background: The Philippines was cited by the WHO as one of the 22 high burden countries in the world which account for 80%of the World's Tuberculosis (TB) cases. The three main reasons why TB remains uncontrolled in the Philippines were poor case finding, poor case holding and deficient TB prevention programs (PHILIPPINE CPG 2000). According to the WHO report the Philippines reached the global target of 75% case detection and 85% treatment success which was due to 100% DOTS coverage in the public sector and the implementation of the Private Public Mix DOTS (PPMD) pilot initiatives. (WHO 2008). In spite of the achievements of the DOTS strategy, issues related to health service delivery, patient related factors, socio economic and treatment related factors still persist. These factors have to be identified to ensure that the treatment completion and cure guaranteed by the DOTS strategy will be delivered to TB patients. Objectives: This study combined the theory of planned behavior with the WHO five interacting dimensions of adherence to determine the factors affecting adherence to the treatment plan of TB DOT centers in Angeles City with the following specific objectives:1. To determine the percentage of patients who adhered to the TB DOT center treatment plan namely: a. completion of treatment b. appointment keeping for pick up of medication during the intensive and maintenance phase c. supervised intake of medication during the intensive and maintenance phase d. submission of sputum sample for AFB smear during the course of treatment. 2. To determine the association of adherence as defined in the first objective with the following factors: 1. Socio economic factors (Income, education, employment) 2. Patient related factors (attitude, self efficacy, consequence, intent, social norm, acceptance) 3. Condition related factors (perceived severity, symptoms, motivation) 4. Health care related factors (health system, DOTS providers, facilitating condition. 5. Treatment related factors (regimen, side effects) 3. To determine the proportion of patients whose sputum converted from positive to negative after completion of treatment. Methodology: The study was a prospective cohort among patients seeking consult at the AUFMC DOT center and a government DOT center in Angeles City. A questionnaire was administered before the start of treatment to determine the profile of patients and factors affecting adherence to the TB DOT center treatment plan using the DOTS strategy. After signing the informed consent, a face to face interview was conducted and TB treatment cards were updated on a weekly basis every time the patient picks up his/her medication looking at the adherence of the patients to appointment keeping to pick up their medication, supervised intake of medication and submission of sputum on designated dates. The patients were followed up for 6-8 months until they completed their treatment. Results: Fifty patients were included in the study with a mean age of 38.79 years (SD 13.65) for the completed group and 48.08 years (SD 17.12) for the non completed group. In the completed group, 50% of respondent were in the 18-39 age group, 50% were male, 71% were married, 55% had high school education, 58% were employed, 37% had an individual income of less than PhP 1500.00 per month, 53% were non Philhealth members, 70% had concomitant co morbid condition, 18% were current alcohol drinker, 5% were frequent smokers and 3% were frequent user of illegal drugs. Seventy percent were enrolled at the AUFMC DOT clinic, 71% were new case undergoing treatment regimen 1 (2 months of triple drug therapy followed by two drugs for four months). With regards behavioral measures among those who completed treatment, 61% had high intent to adhere to completion of treatment, 53% had high acceptance of their disease condition and 66% gave a high score on their perception of services at the DOTS center. The success rate which is the sum of patients who completed treatment and was cured and patients who completed treatment without cure was estimated at 76% (95% CI 61.8-87.0).The percentage of patients who kept at least 80% of their appointments to pick up their medication are 94% in the intensive phase which is higher than the maintenance phase at 60%. The percentage of patients who took at least 80% of their medication is 98% in the intensive phase which is higher that the maintenance phase at 76%. Forty four percent of patients (95% CI 30-48.7) submitted sputum sample at the end of treatment. With regards to the factors affecting completion of treatment, multiple logistic regression analysis showed that the odds of completing treatment is 0.05 (95% CI 0.002-1.20) among those who had adverse effect controlling for the confounding of previous history of smoking, presence of co morbid condition, age 50 years old or more and frequent alcohol intake. The odds of keeping appointment to pick up medication is 0.22 (95% CI 0.05-1.03) among those who are of female gender controlling for the confounding of site of DOT provider and attitude. The odds of drug intake is 0.32 (95% CI 0.04-2.54) among those who are using illegal drugs controlling for the confounding of the presence of co morbid condition and site of DOTS provider. The odds of sputum submission is 23.26 (95% CI 2.29-235.40) among those who were classified as having relapse controlling for the confounding of previous history of smoking, current history of smoking and having positive attitude towards the DOTS center treatment plan. The percentage of patients whose sputum converted from positive to negative was 29% (95% CI; 8.4-58.1) and the cure rate which is defined as the number of patients who had at least one negative sputum before and at the end of treatment was estimated at 44% (95% CI; 30-48.7). Conclusion and Recommendations: The results of the study suggest that the treatment success rate of DOTS clinic in Angeles City was below the WHO target and the National success rate. The percentage of patients who adhered to their appointment to pick up their medication and intake of medication during the maintenance phase was low. The exact cure rate at the end of treatment cannot be ascertained because the number of patients submitting sputum at the end of treatment was low. In spite of the DOTS strategy, adherence to treatment and sputum submission was way below the target. The common belief that the patients are solely responsible for non-adherence is misleading as shown in the study. Four of the five dimensions of adherence namely patient related, condition related, treatment realted and health service related factors were found to influence the completion of treatment, pick-up, intake of medication and sputum submission. Perhaps a better approach to improve adherence is to explore the factors affecting adherence through systematic identification of all the processes involved in the TB DOT Center treatment plan. After identification of the processes, a lock-in mechanism to consolidate corrective actions is instituted to ensure provision of quality health care to all patients enrolled in the TB DOT center. Furthermore, improving certification and accreditation standards will increase the quality of health care provided to TB patients. A re-orientation of job description of each member of the TB DOT center team is also recommended in order to educate the patient in all aspects of the treatment plan. Lastly, sputum submission is an important processes to establish cure therefore factors affecting adherence to submission should be agresively sought.